Simultaneous superresolution reconstruction and distortion correction for single‐shot EPI DWI using deep learning. Issue 6 (27th January 2023) - Ye, Xinyu; Wang, Peipei; Li, Sisi; Zhang, Jieying; Lian, Yuan; Zhang, Yajing; Lu, Jie; Guo, Hua
Abstract : Purpose: Single‐shot (SS) EPI is widely used for clinical DWI. This study aims to develop an end‐to‐end deep learning–based method with a novel loss function in an improved network structure to simultaneously increase the resolution and correct distortions for SS‐EPI DWI. Theory and Methods: Point‐spread‐function (PSF)–encoded EPI can provide high‐resolution, distortion‐free DWI images. A distorted image from SS‐EPI can be described as the convolution between a PSF function with a distortion‐free image. The deconvolution process to recover the distortion‐free image can be achieved with a convolution neural network, which also learns the mapping function between low‐resolution SS‐EPI and high‐resolution reference PSF‐EPI to achieve superresolution. To suppress the oversmoothing effect, we proposed a modified generative adversarial network structure, in which a dense net with gradient map guidance and a multilevel fusion block was used as the generator. A fractional anisotropy loss was proposed to utilize the diffusion anisotropy information among diffusion directions. In vivo brain DWI data were used to test the proposed method. Results: The results show that distortion‐corrected high‐resolution DWI images with restored structural details can be obtained from low‐resolution SS‐EPI images by taking advantage of the high‐resolution anatomical images. Additionally, the proposed network can improve the quantitative accuracy of diffusion metrics compared with previously reported networks. Conclusion: Using high‐resolution, distortion‐free EPI‐DWI images as references, a deep learning–based method to simultaneously increase the perceived resolution and correct distortions for low‐resolution SS‐EPI was proposed. The results show that DWI image quality and diffusion metrics can be improved.